PGD-VTCR - Barbarulo, Andrea (Strojniški vestnik, 2014)
The calculation of vibrational responses of complex systems on frequency bands appears to be more and more important in engineering simulation. This is particularly true in the medium frequency regime where the solution is very sensitive to the frequency. In this work, we propose a new path to determine the frequency response of a system at many frequencies. It is based on the variational theory of complex rays (VTCR), a mid frequency dedicated numerical strategy, and the proper generalized decomposition (PGD), a model order reduction technique. The VTCR enables one to model the problem thanks to the use of waves, and the PGD expands the VTCR approximation over the frequency band through a separated variable representation. This strategy is illustrated on a 2-D acoustic car cavity example.
Keywords: akustika; generalizirana dekompozicija; redukcija modela; srednje frekvenčno območje; variacijska teorija